JUDICIAL REVIEW OF GOVERNMENT REGULATIONS IN LIEU OF LAWS PROBLEMS - Ali Marwan Hsb (NOMOI Law Review, 2021)
The granting of the authority for judicial review of government regulations in lieu of laws to the Constitutional Court through Decision Number 138 / PUU-VII / 2009 in addition to being a legal breakthrough in filling the legal void for reviewing statutory regulations, in practice creates problems. The Method use in thisWhere, the verdict of examining government regulations in lieu of law is unacceptable because the petition loses its object as a result of the passage of government regulations in lieu of law as the object of examination into law.Keywords: Judicial Review, Government Regulations in Lieu of Law, Constitutional Court.